Differential expression patterns of leukaemia associated genes in leukaemia cell lines compared to healthy controls - Ang, Pei Shen; Ramasamy, Rajesh; Hussin, Noor Hamidah; Cheong, Soon Keng; Seow, Heng Fong; Abdullah, Maha (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Introduction: The phenotype and genotype of cancer cells portray hallmarks of cancer which may have clinical value. Cancer cell lines are ideal models to study and confirm these characteristics. We previously established two subtracted cDNA libraries with differentially expressed genes from an acute myeloid leukaemia patient with poor prognosis (PP) and good prognosis (GP). Objective: To compare gene expression of the leukaemia associated genes with selected biological characteristics in leukaemia cell lines and normal controls. Methodology: Expression of 28 PP genes associated with early fetal/embryonic development, HOX-related genes, hematopoiesis and aerobic glycolysis/hypoxia genes and 36 GP genes involved in oxidative phosphorylation, protein synthesis, chromatin remodelling and cell motility were examined in B-lymphoid (BV173, Reh and RS4;11) and myeloid (HL-60, K562) leukaemia cell lines after 72h in culture as well as peripheral blood mononuclear cells from healthy controls (N=5) using semi-quantitative polymerase chain reaction (PCR) method. Cell cycle profiles were analysed on flow cytometry while MTT cytotoxicity assay was used to determine drug resistance to epirubicin. Results: Genes expressed significantly higher in B-lymphoid leukaemia cell lines compared to healthy controls were mostly of the GP library i.e. oxidative phosphorylation (3/10), protein synthesis (4/11), chromatin remodelling (3/3) and actin cytoskeleton genes (1/5). Only two genes with significant difference were from the PP library. Cancer associated genes, HSPA9 and PSPH (GP library) and BCAP31 (PP library) were significantly higher in the B-lymphoid leukemia cell lines. No significant difference was observed between myeloid cell lines and healthy controls. This may also be due heterogeneity of cell lines studied. PBMC from healthy controls were not in cell cycle. G2/M profiles and growth curves showed B-lymphoid cells just reaching plateau after 72 hour culture while myeloid cells were declining. IC50 values from cytotoxicity assay revealed myeloid cell lines had an average 13-fold higher drug resistance to epirubicin compared to B-lymphoid cell lines. Only CCL1, was expressed at least two-fold higher in myeloid compared to B-lymphoid cell lines. In contrast, MTRNR2, EEF1A1, PTMA, HLA-DR, C6orf115, PBX3, ENPP4, SELL, and IL3Ra were expressed more than 2-fold higher in B-lymphoid compared to myeloid cell lines studied here. Conclusion: Thus, B-lymphoid leukaemia cell lines here exhibited active, proliferating characteristics closer to GP genes. Higher expression of several genes in B-lymphoid compared to myeloid leukaemia cell lines may be useful markers to study biological differences including drug resistance between lineages.